PENGUKURAN KINERJA PERBANKAN SYARIAH DENGAN MENGGUNAKAN PENDEKATAN INDEKS MAQASHID SYARIAH - AHMAD WIRA; HEFRIZAL HANDRA; ALFI SYUKRIA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to analyze Islamic banking financial performance in Indonesia using the Maqasid Syariah Index method. A behavioral operationalization approach method is used to determine the maqasid sharia index performance indicators on Islamic banks which are then used for testing on samples from the Bank Nagari Sharia Business Unit. Banks are evaluated and at three levels based on their rank: 1) performance ratio, 2) performance indicators and 3) overall Maqasid Index. For the measurement of the Maqasid Islamic index this study uses a quantitative method The Simple Additive Weighting or weighted sum method. The results of the study indicate that Islamic banks have a performance of 11.52%.